Enhancing palliative care delivery in a regional community in Australia - Phillips, J.; Davidson, Patricia; Jackson, D.; Kristjanson, Linda; Bennett, M.; Daly, J. (Australian Healthcare and Hospitals Association, 2006)
Although access to palliative care is a fundamental right for people in Australia and is endorsed by government policy, there is often limited access to specialist palliative care services in regional, rural and remote areas. This article appraises the evidence pertaining to palliative care service delivery to inform a sustainable model of palliative care that meets the needs of a regional population on the mid-north coast of New South Wales.Expert consultation and an eclectic literature review were undertaken to develop a model of palliative care service delivery appropriate to the needs of the target population and resources of the local community. On the basis of this review, a local palliative care system that is based on a population-based approach to service planning and delivery, with formalised integrated network agreements and role delineation between specialist and generalist providers, has the greatest potential to meet the palliative care needs of this regional coastal community.